HIV awareness among first year MBBS students in a private medical college, Telangana, India - Shridevi, Kotina; Srigouri, Talikota (International Journal Of Community Medicine And Public Health, 2017)
Background: Globally, since 1980, 70 million people were infected with HIV virus and 33.3 million people have died of HIV. In Sub-Saharan Africa, largest number of people living with HIV is Asia. In these areas 19 million of the 35 million people living with the virus globally do not know their HIV positive status. The objectives of the study were to know the awareness regarding HIV and its mode of transmission, clinical features and diagnosis of HIV, prevention and vaccine availability of HIV. Methods: Study design: cross sectional study, study area: private medical college, Telangana state, study population- 136 students in the 1st year MBBS. Methodology: The data was collected by a pre designed, pretested and semi structured questionnaire which consisted of, identification data, HIV Awareness, mode of transmission, symptoms and diagnosis, prevention and vaccine availability of HIV. The data was analyzed by using Microsoft Excel. Results: Males and females in the study were 43.38% and 56.6% respectively. Mean age of students was 18.184. 100% of the students heard about HIV, 25% of the students did not know that HIV and AIDS are different stages of the same disease. 98.52% were aware that contaminated needles and syringes as route of transmission, 87.5% were aware about vertical transmission. 93.38% of the students have a correct opinion that avoiding multiple partners’. 80.88% knew that antiretroviral drugs are available. 91.91% knew that the vaccine is not yet available for HIV. Conclusions: There is overall satisfactory level of awareness on routes of transmission and prevention of HIV/AIDS but knowledge regarding symptoms is less. There were several misconceptions regarding route and Prevention of HIV. Very few knew that immediate medical attention will prevent HIV.